2016
DOI: 10.1101/gad.274134.115
|View full text |Cite
|
Sign up to set email alerts
|

Atg7 cooperates with Pten loss to drive prostate cancer tumor growth

Abstract: Understanding new therapeutic paradigms for both castrate-sensitive and more aggressive castrate-resistant prostate cancer is essential to improve clinical outcomes. As a critically important cellular process, autophagy promotes stress tolerance by recycling intracellular components to sustain metabolism important for tumor survival. To assess the importance of autophagy in prostate cancer, we generated a new autochthonous genetically engineered mouse model (GEMM) with inducible prostate-specific deficiency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 29 publications
5
82
1
Order By: Relevance
“…In a GEMM for castrate-naïve prostate cancer driven by Pten deficiency, Atg7 deficiency suppresses tumor growth (Santanam et al 2016). Atg7 deficiency increases endoplasmic reticulum stress and reduces tumor cell proliferation.…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In a GEMM for castrate-naïve prostate cancer driven by Pten deficiency, Atg7 deficiency suppresses tumor growth (Santanam et al 2016). Atg7 deficiency increases endoplasmic reticulum stress and reduces tumor cell proliferation.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Atg7 deficiency increases endoplasmic reticulum stress and reduces tumor cell proliferation. Importantly, overall mouse survival is increased by Atg7 deficiency in prostate tumors, and castrate-resistant disease is also suppressed by Atg7 loss (Santanam et al 2016).…”
Section: Prostate Cancermentioning
confidence: 99%
“…However, lung-specific ATG7 deficiency inhibits Kras G12D -driven lung tumor growth and reduction of lung tumor burden with dysfunctional mitochondria and proliferative arrest 5 . ATG7 deficiency produces an autophagy-deficient phenotype and inhibits PTEN (phosphatase and tensin homolog)-deficient prostate tumor progression through management of protein homeostasis under endoplasmic reticulum (ER) stress 6 . Additionally, in our most recent studies, we have shown that ATG7 and its mediated autophagy were much higher in human BC cell lines and N-Butyl-N-(4-hydmoxybutyl)nitrosamine (BBN)-treated UROtsa cells as well as in BBN-induced mouse invasive BCs, which play a promotive role in human BC invasion (J.Z., unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…In other GEMMs for cancer, autophagy promotes the growth of Braf V600E -induced lung tumors (Strohecker and White 2014) and Pten-deficient prostate tumors (Santanam et al 2016) and suppresses senescence in melanomas driven by Braf V600E and loss of Pten (Xie et al 2015). Genetic loss of autophagy impairs the progression of Kras-driven premalignant pancreatic intraepithelial neoplasia (PANIN) lesions to invasive cancer (Rosenfeldt et al 2013;Yang et al 2014).…”
mentioning
confidence: 99%